Knowledge for innovation: creative routines and weak signal processing. (18th March 2021) - Fachinelli, Ana Cristina; Ribeiro, Jairo Moran Carvalho; D'Arrigo, Fernanda
The monitoring of business environments allows companies to identify signals that, when processed, become external stimulation to the creative process and innovation sources. This study aimed to investigate the use of creative routines for signal processing and innovation performance in a corporate group. The research is based on a case study carried out in six companies which are part of a Brazilian corporate group. The methodology used was mixed methods with the concurrent embedded design. We collected qualitative and quantitative data in multiple units of analysis. The results indicate that companies that have developed creative routines perform better on innovation. They also reveal that innovation agents act locally and around their environment. Therefore, there is an endogenous potential for the use of creative routines to foster innovation.